Influence of physical activity and nutrition on sleep quality of Romanian students: a case study - Barna, Octavian; Plesea-Condratovici, Alina; Oltean, Antonela; Popescu, Raducu; Gidu, Diana Victoria; Duta, Daniel; Turcu, Ioan; Circiumaru, Dan; Varzaru, Cristina (Progress in Nutrition, 2022)
Sleep problems are associated with poorer quality of life, as well as mental and physical health issues, especially in people who are overweight or obese. Numerous studies have shown that there is a link between sleep and diet and between sleep and physical activity (PA). The present study aimed to show the connection between physical activity, diet, and the quality and duration of sleep in Romanian students. The main study was conducted on 876 students (435 women and 441 men) aged 19–26. Three weeks after the start of the main study, a subset of 83 male and female students aged 19–25 years were randomly selected to participate in an ancillary study. A questionnaire survey was conducted in order to determine the quality of sleep (PSQI), nutritional habits (HEI Index 2005), and physical activity (IPAQ), while anthropometric measurements were performed to determine body mass index (BMI). For students involved in the main study, PSQI varied between 6.4(2.3) and 4.5(1.7) and PA from 409.15(108.12) to 5834.54(2548.32) MET. The number of hours of sleep varied between 6.8(2.2) and 7.6(1.8). The HEI index varied between 52.1(12.2) and 55.3(11.4), being directly proportional to the increase in sleep quality and the number of daily sleep hours. Similar results were obtained for the ancillary study. Statistical analyses were performed using SPSS version 23 (SPSS, Inc. Chicago, IL); a value of 5% was set as the conventional significance level. ANOVA was used to identify statistically significant differences between averages of variables for the groups. For all variables analyzed, t tests showed no significant differences between females and males as p > α = 0.05 and the 95% confidence interval contained the value 0.